The Effect of Al-Qur'an Al-Rahman Murottal Therapy on Reducing Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus in the Working Area of the Telaga Biru Health Center - Nurliah Nurliah; Hamna Vonny Lasanuddin; Sri Yulian Hunowu; Salahudin Pakaya; Husain Rahmat (Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the effect of al-Qur'an Ar-Rahman murottal therapy on reducing blood sugar levels in patients with type 2 diabetes mellitus. This research uses the design of an experiment Pre-Post One Group. The sample was taken by simple random sampling technique with odd-numbered respondents (1,3,5,7,9 etc.) with a sample of 22 respondents. Data collection using observation sheets and data analysis using the Wilcoxon test with a meaning level of 95% (a = 0.05). The results of this study showed that blood sugar levels decreased from Pre-Test to Post-Test with Mean Ranks of 11.50 and statistical test results were obtained p = 0.000 (p < 0.05) so that it can be concluded that there is an influence of Qur'an murottal therapy on reducing blood sugar levels in patients with type 2 diabetes mellitus